The Host Gaze in Global Tourism 2012
DOI: 10.1079/9781780640211.0047
|View full text |Cite
|
Sign up to set email alerts
|

Turkish host gaze at Russian tourists: a cultural perspective.

Abstract: This chapter examines Turkish hoteliers' gaze at Russian tourists visiting the south coast of Turkey. The gaze of the owners, managers and employees of all-inclusive resorts and hotels in the holiday districts of Antalya is analysed. The reasons for the specific host gaze are explained by focusing on cultural identity of Russian tourists and cultural underpinning of their behaviour. The chapter shows how cultural misperceptions and misunderstandings between hosts and tourists can upset the hosts and create a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…Whilst earlier research identified different forms of host-guest relations ranging from frequent, commercial exchanges to informal encounters (e.g. Krippendorf, 1987), lateral work concludes that the host-guest relationship is largely conditioned by its commercial nature (Reisinger et al, 2013). In this regard, the terms 'service provider' and 'customer' were proposed as more appropriate to describe the roles of each party (Aramberri, 2001).…”
Section: Power In Hospitality and Tourism Studiesmentioning
confidence: 99%
“…Whilst earlier research identified different forms of host-guest relations ranging from frequent, commercial exchanges to informal encounters (e.g. Krippendorf, 1987), lateral work concludes that the host-guest relationship is largely conditioned by its commercial nature (Reisinger et al, 2013). In this regard, the terms 'service provider' and 'customer' were proposed as more appropriate to describe the roles of each party (Aramberri, 2001).…”
Section: Power In Hospitality and Tourism Studiesmentioning
confidence: 99%
“…Unfriendly, demanding, bad habits, suspicious… is how a German travel website, and 40 % of Europeans who traveled to Turkey or Egypt, the most popular Russian destinations, described Russians at the same hotel (Ageenko, Papazyan & Apukhtin, 2013). Another study explains this view, that while traveling Russians do not speak English (incapable or unwilling), and even if they do, do not want to communicate with other people, which make others perceive Russians as rude (Reisinger, Kozak & Visser, 2013). The authors continue that Russian tourists are loud, have bad manners and always want to act freely.…”
Section: Russian Touristsmentioning
confidence: 95%
“…To begin with the Turkish market, compared to German and Turkish tourists in Turkey, Russians seem unaware about environmental issues and these issues do not influence their travel choices (Baysan, 2001). Turkish hosts judged Russian tourists according to single cases and their stereotypes, not taking into account Russian culture (Reisinger, Kozak & Visser, 2013). Another study showed that accommodation services play the most important role for Russian tourists' satisfaction in Turkey.…”
Section: Russian Touristsmentioning
confidence: 99%
“…Moufakkir and Reisinger (2013), in their edited collection of works on the host gaze, provide evidence that host gaze studies offer the potential for deeper, more inclusive, and more transparent analysis of political realities in tourist destination. Host gaze studies in this volume have contributed to understanding of cross-cultural relations between hosts and tourists (Reisinger et al, 2013); interfaith relations (Gelbman and Collins-Kreiner, 2013); indigenous perspectives on visitors (Bunten, 2103); and general understanding of otherness (Ankor and Wearing, 2013).…”
Section: The Host Gaze Literature Solidifiesmentioning
confidence: 97%
“…Host gaze studies in this volume have contributed to understanding of cross-cultural relations between hosts and tourists (Reisinger et al, 2013); interfaith relations (Gelbman and Collins-Kreiner, 2013); indigenous perspectives on visitors (Bunten, 2103); and general understanding of otherness (Ankor and Wearing, 2013).…”
Section: The Host Gaze Literature Solidifiesmentioning
confidence: 99%